Raman Spectroscopy Enables Non-invasive and Confirmatory Diagnostics of Aluminum and Iron Toxicities in Rice - Higgins, Samantha; Biswas, Sudip; Goff, Nicolas K.; Septiningsih, Endang M.; Kurouski, Dmitry (Frontiers in Plant Science, 2022)
Metal toxicities can be detrimental to a plant health, as well as to the health of animal and humans that consume such plants. Metal content of plants can be analyzed using colorimetric, atomic absorption- or mass spectroscopy-based methods. However, these techniques are destructive, costly and laborious. In the current study, we investigate the potential of Raman spectroscopy (RS), a modern spectroscopic technique, for detection and identification of metal toxicities in rice. We modeled medium and high levels of iron and aluminum toxicities in hydroponically-grown plants. Spectroscopic analyses of their leaves showed that both iron and aluminum toxicities can be detected and identified with ~100% accuracy as early as day two after the stress initiation. We also showed that diagnostics accuracy was very high not only on early, but also on middle (day four- day eight) and late (day ten- day fourteen) stages of the stress development. Importantly this approach only requires an acquisition time of one second; it is non-invasive and non-destructive to plants. Our findings suggest that if implemented in farming, RS can enable pre-symptomatic detection and identification of metallic toxins that would lead to faster recovery of crops and prevent further damage.